Objective intestinal function in patients with idiopathic REM sleep behavior disorder. (January 2019) - Knudsen, Karoline; Fedorova, Tatyana D.; Hansen, Allan K.; Sommerauer, Michael; Haase, Anne-Mette; Svendsen, Kristina B.; Otto, Marit; Østergaard, Karen; Krogh, Klaus; Borghammer, Per
Abstract: Background: Parkinson's disease is characterized by pathological α-synuclein accumulation and cell death, which has been hypothesized to originate in peripheral nerve terminals and subsequently spread via autonomic nerves. Supporting this, most Parkinson's disease patients experience autonomic non-motor symptoms such as constipation, often years prior to diagnosis. Objective: We aimed to study gastrointestinal transit time, colonic volume, and peristaltic movements in idiopathic REM Sleep Behavior Disorder patients, a prodromal marker of Parkinson's disease or Dementia with Lewy bodies. Methods: Twenty-two patients were included and compared to previously published data from Parkinson's disease patients and controls. Gastrointestinal transit time, computed tomography-based volume estimation, and colonic motility were performed as markers of gastrointestinal function and autonomic involvement. Subjective constipation symptoms were evaluated with two different questionnaires. Results: Gastrointestinal transit time was increased in 33% (p = 0.039) and colonic volume in 48% (p = 0.0049) of patients. Colonic transit time measured by the 3D-Transit system was increased in 70% (p = 0.0326) and the number of fast peristaltic colonic movements was reduced (p = 0.015). Mean small intestinal transit time was comparable to Parkinson's disease patients, although not significantly different compared to controls (p = 0.18). Subjective constipation symptoms were present in 18 or 41%, depending on type of questionnaire. Conclusions: Total gastrointestinal transit time, colonic volume, and 3D-Transit colonic transit time were significantly increased compared to controls, although not to the extent seen in medicated Parkinson's patients. Limited correlation was seen between subjective constipation and objective markers. The findings support that marked GI dysfunction is present in the early prodromal PD phase. Highlights: Significantly increased total gastrointestinal transit time was seen in iRBD patients. Colonic volume was significantly increased in iRBD patients. Small intestinal transit time was increased in iRBD, although not significantly. Limited correlation was seen between subjective constipation and objective markers.